2012
DOI: 10.1111/eth.12018
|View full text |Cite
|
Sign up to set email alerts
|

Reward Tracking and Memory Decay in the Monarch Butterfly, Danaus plexippus L. (Lepidoptera: Nymphalidae)

Abstract: Due to their long‐distance migration routes and high longevity, monarch butterflies (Danaus plexippus) are likely to benefit from learning how to discriminate and remember suitable feeding resources. In this study, we assessed monarchs’ abilities to track changing nectar sources over time and to retain learned information presented in two conditioning schedules. Non‐preferred (blue and red) and preferred (yellow) artificial flowers were concomitantly offered to monarchs in a three‐phase experiment. In each pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 44 publications
0
14
1
Order By: Relevance
“…2). Agents have a perceptual range assumed to represent the distance that they can detect milkweed plants through olfactory or visual cues (Bergstrom et al, 1994;Garlick, 2007;Rodrigues and Weiss, 2012). Wild monarchs likely use olfaction for long-range detection of milkweed, and visual cues at short distances (Garlick, 2007).…”
Section: Submodelsmentioning
confidence: 99%
See 2 more Smart Citations
“…2). Agents have a perceptual range assumed to represent the distance that they can detect milkweed plants through olfactory or visual cues (Bergstrom et al, 1994;Garlick, 2007;Rodrigues and Weiss, 2012). Wild monarchs likely use olfaction for long-range detection of milkweed, and visual cues at short distances (Garlick, 2007).…”
Section: Submodelsmentioning
confidence: 99%
“…If more than one patch is detected within the perceptual range, the agent must choose which patch to move toward (i.e., decisional flight). Monarch agents are assumed to have a higher probability of moving toward patches with higher milkweed density, based on laboratory and greenhouse studies suggesting that increased number of milkweed plants result in an increased intensity of olfactory and/or visual cues (Bergstrom et al, 1994;Rodrigues and Weiss, 2012;Garlick, 2007). Monarch agent attractiveness to a patch is based on the milkweed density parameter, after adjustments.…”
Section: Submodelsmentioning
confidence: 99%
See 1 more Smart Citation
“…But in this study, yellow flowers ( Ranunculus acris especially) were frequently visited by other butterfly species. This is confirmed by other studies; examples include Thymelicus flavus (Goulson et al ., ), Battus philenor (Weiss, ), Danaus plexipus (Rodrigues & Weiss, ) and Lysandra bellargus (Rusterholz & Erhardt, ). Our results are in line with sex‐specific flower colour preferences.…”
Section: Discussionmentioning
confidence: 99%
“…The southern monarch is closely related to the temperate monarch butterfly Danaus plexippus, as both species belong to the subgenus Danaus (Brower et al 2010;Hay-Roe et al 2007;Smith et al 2005). Associative color learning (Blackiston et al 2011;Rodrigues et al 2010a), aversive learning and risk aversion (Rodrigues et al 2010a), as well as memory capacity (Rodrigues and Weiss 2012), have been shown for D. plexippus in the context of feeding. Taken together, these studies indicate that these sister species may have similar cognitive abilities.…”
Section: Introductionmentioning
confidence: 99%